2021
DOI: 10.3390/en14164725
|View full text |Cite
|
Sign up to set email alerts
|

Food Production Security in Times of a Long-Term Energy Shortage Crisis: The Example of Poland

Abstract: In countries with industrialized agriculture, the contribution of fossil energy equals or exceeds the energy provided to society in food. Poland is one of the countries which, in the absence of its own sufficient oil and gas resources, is forced to import these fossil fuels in order to benefit from modern solutions in the field of food production and distribution. This situation poses a serious threat to food security if there is a prolonged shortage of energy from such sources. Using the example of Poland, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…This affected its optical properties, and the PCE of the BDT (T) (6.5%) and BDT (S) (4.7%) was significantly higher than that of the BDT (F) (3.0%). Intemann [81] et al used selenophene to replace thiophene in the core, and then copolymerized with 4,7-dibromo-5,6difluoro- [1][2][3] benzothiadiazole to obtain a new polymer, PIDSe-DFBT. Compared with the original PIDT-DFBT (1.88 eV), the optical gap of PIDSe-DFBT (1.80 eV) was smaller.…”
Section: Polymer Donor With Selenophene As Side Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…This affected its optical properties, and the PCE of the BDT (T) (6.5%) and BDT (S) (4.7%) was significantly higher than that of the BDT (F) (3.0%). Intemann [81] et al used selenophene to replace thiophene in the core, and then copolymerized with 4,7-dibromo-5,6difluoro- [1][2][3] benzothiadiazole to obtain a new polymer, PIDSe-DFBT. Compared with the original PIDT-DFBT (1.88 eV), the optical gap of PIDSe-DFBT (1.80 eV) was smaller.…”
Section: Polymer Donor With Selenophene As Side Chainmentioning
confidence: 99%
“…With the development of the world economy, energy resources are becoming more and more scarce [1], and solar cells, as new energy materials, have a good development prospect in this area. Solar cells have always been a research hotspot, but also a technical problem, which also makes them the focus of attention all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of studies have demonstrated the high dependence of agriculture production and energy supply (e.g., Arizpe et al, 2011;Ghisellini et al, 2016;Buko et al, 2021), even through agriculture accounts for only a relatively small proportion of total final energy demand. Consequently, energy supply would also play a key role in agriculture production especially for farm machinery and irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…After the two industrial revolutions, the economy of human society began to develop at an accelerating speed, and the energy utilization modes are upgrading continuously. As a result, now all countries around the globe are facing two prominent problems: energy shortage and environmental pollution [5][6][7][8][9]. Due to the limited technological level and the historical problems of traditional industrial development mode, China's industrial production and manufacturing processes generally have problems such as high resource consumption and large energy waste.…”
Section: Introductionmentioning
confidence: 99%